A Power Theory of Third Party Intervention in Labour Management Relations - Hameed, Syed; Sen, Joya (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
The authors present theoretical constructs of power and theoretical concepts as they apply to motivation, conflict and negotiation.